Correlation of Insulin Resistance with Anthropometric Measures and Blood Pressure in Adolescents - Morais,Polyana Resende Silva de (2016)
Abstract Background: Blood pressure is directly related to body mass index, and individuals with increased waist circumference have higher risk of developing hypertension, insulin resistance, and other metabolic changes, since adolescence. Objective: to evaluate the correlation of blood pressure with insulin resistance, waist circumference and body mass index in adolescents. Methods: Cross-section study on a representative sample of adolescent students. One group of adolescents with altered blood pressure detected by casual blood pressure and/or home blood pressure monitoring (blood pressure > 90th percentile) and one group of normotensive adolescents were studied. Body mass index, waist circumference were measured, and fasting glucose and plasma insulin levels were determined, using the HOMA-IR index to identify insulin resistance. Results: A total of 162 adolescents (35 with normal blood pressure and 127 with altered blood pressure) were studied; 61% (n = 99) of them were boys and the mean age was 14.9 ± 1.62 years. Thirty-eight (23.5%) adolescents had altered HOMA-IR. The group with altered blood pressure had higher values of waist circumference, body mass index and HOMA-IR (p<0.05). Waist circumference was higher among boys in both groups (p<0.05) and girls with altered blood pressure had higher HOMA-IR than boys (p<0.05). There was a significant moderate correlation between body mass index and HOMA-IR in the group with altered blood pressure (ρ = 0.394; p < 0.001), and such correlation was stronger than in the normotensive group. There was also a significant moderate correlation between waist circumference and HOMA-IR in both groups (ρ = 0.345; p < 0.05). Logistic regression showed that HOMA-IR was as predictor of altered blood pressure (odds ratio - OR = 2.0; p = 0.001). Conclusion: There was a significant association of insulin resistance with blood pressure and the impact of insulin resistance on blood pressure since childhood. The correlation and association between markers of cardiovascular diseases was more pronounced in adolescents with altered blood pressure, suggesting that primary prevention strategies for cardiovascular risk factors should be early implemented in childhood and adolescence.